Non-Alcoholic Fatty Liver Disease and Hypothyroidism: Review of Clinical and Experimental Studies - Tetiana Ranhulova (Ivano-Frankivsk National Medical University, 2021)
Hypothyroidism is a widespread condition affecting people of different socio-economic background and geographical location. A lot of studies highlight the effect of hypothyroidism on the metabolic processes in various organs, including the liver. On the other hand, liver damage often results in the development of non-alcoholic fatty liver disease; however, the data on the impact of hypothyroidism on liver morphology, which can serve as a direct indicator and marker of liver condition and function, are limited and controversial. In this report, we reviewed the relationship between non-alcoholic fatty liver disease and hypothyroidism with an accent on morphological alteration of the liver discovered in clinical and experimental studies.